Design Application Performance Assessment Web base in PT E-T-A Indonesia - Munib, Achmad; Tiowati, Sulis; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. E-T-A Indonesia is a subsidiary of international company from Germany which are engaged in the design and production circuit breaker that aims to give solution an electric current protection. The problem in PT. E-T-A Indonesia is process of performance assessment obstructed because MD and GM often out of town so that the HRD have to postpone the assessment. Then, next problem is too many performance assessment sheets to be done that caused HRD difficulty in performing calculations and archiving the assessment results.To overcome the problem of above, performance assessment needs to be converted to digital and computerized data. To fulfill the need of it has to be made an web-based application of performance assessment in PT. E-T-A Indonesia. Performance assessment application making uses the System Development Life Cycle (SDLC).The result of research showed this application can support the process of employees’ recommendation, value and recommendation results recapitulation. Other than that, this application can also produce employees’ report as employees recommendation data. Keywords : application, performance assessment, recommendation